THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE SUCCESS OF EXCLUSIVE BREASTFEEDING: LITERATURE REVIEW - Pratama, Benny Putra; Fajar, Nur Alam; Idris, Haerawati; Fatmalina Febry; Rini Mutahar; Suci Destriatania (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Exclusive breastfeeding is a key strategy for improving infant health and survival; however, its achievement remains suboptimal in many countries. Family support has been consistently identified as a major interpersonal determinant influencing exclusive breastfeeding success, highlighting the need for a comprehensive synthesis of recent empirical evidence. This study aims to examine and synthesize findings from empirical research on the role of family support in exclusive breastfeeding success through a narrative literature review. Literature searches were conducted using PubMed, ScienceDirect, and Google Scholar, covering publications from 2020 to 2025. Of the 864 articles initially identified, 15 studies were selected based on predefined inclusion criteria and substantive relevance to the review focus. The synthesis indicates that family support, particularly from husbands and extended family members, is consistently associated with higher exclusive breastfeeding success, with reported odds ranging from approximately two to more than threefold across studies. Family support contributes to enhanced breastfeeding self efficacy, reduced postpartum stress, decreased prelacteal feeding practices, and the establishment of a supportive home environment for breastfeeding. The mechanisms underlying these effects involve interacting psychological, hormonal, and social pathways. These findings underscore the importance of family centered approaches in exclusive breastfeeding promotion, suggesting that health interventions should not focus solely on mothers but actively engage husbands and family members as key partners in supporting breastfeeding practices